Additive Engineering for High‐Performance Two‐Dimensional Dion–Jacobson Pb–Sn Alloyed Perovskite Solar Cells. Issue 12 (21st October 2022) - Shi, Hongxi; Zhang, Lei; Huang, Hao; Ou, Yali; Wang, Xiaoting; Li, Ziyu; Chi, Dan; Huang, Shihua
Abstract : Two‐dimensional perovskite materials attract great attentions for the application of perovskite solar cells (PSCs) due to the regulable bandgap and high stability. However, the power conversion efficiency (PCE) of 2D PSCs is far behind in that of three‐dimensional PSCs. Herein, Dion–Jacobson (DJ) phase Pb–Sn perovskite of (PhDMA)MA4 (Pb0.5 Sn0.5 )5 I16 in 2D PSCs is introduced, which has suitable bandgap of 1.27 eV and offers the candidate for the absorber of bottom device in all perovskite tandem solar cells. The nonlinear bandgap behavior of 2D Pb–Sn perovskite materials is certified by adjusting the recipe of precursors to vary the bandgap of perovskite films. Moreover, MACl is employed to improve the film quality of 2D Pb–Sn perovskite, leading to the suppression of the defect density and nonradiative recombination for 2D PSCs. As a result, a high PCE of 12.2% is achieved for DJ phase 2D Pb–Sn PSCs. Abstract : Herein, the nonlinear bandgap behavior of 2D Pb–Sn perovskite materials is demonstrated. Moreover, MACl is introduced to improve the film quality of Dion–Jacobson phase 2D Pb–Sn perovskite with (PhDMA)MA4 (Pb0.5 Sn0.5 )5 I16, resulting in the suppression of the defect density and the nonradiative recombination. Consequently, high power conversion efficiency of 12.2% is achieved for 2D Pb–Sn perovskite solar cell.